The effects of robot facial emotional expressions and gender on child–robot interaction in a field study. Issue 4 (2nd October 2018) - Cameron, David; Millings, Abigail; Fernando, Samuel; Collins, Emily C.; Moore, Roger; Sharkey, Amanda; Evers, Vanessa; Prescott, Tony
ABSTRACT: Emotions, and emotional expression, have a broad influence on social interactions and are thus a key factor to consider in developing social robots. This study examined the impact of life-like affective facial expressions, in the humanoid robot Zeno, on children's behaviour and attitudes towards the robot. Results indicate that robot expressions have mixed effects depending on participant gender. Male participants interacting with a responsive facially expressive robot showed a positive affective response and indicated greater liking towards the robot, compared to those interacting with the same robot maintaining a neutral expression. Female participants showed no marked difference across the conditions. We discuss the broader implications of these findings in terms of gender differences in human–robot interaction, noting the importance of the gender appearance in robots (in this case, male) and in relation to advancing the understanding of how interactions with expressive robots could lead to task-appropriate symbiotic relationships.